1974
DOI: 10.1056/nejm197401032900102
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Prophylaxis in a Boarding School

Abstract: A double-blind study to evaluate vitamin C supplements for respiratory-infection prophylaxis was conducted among 641 children at a Navajo boarding school over a 14-week period. Supplements of 1 and 2 g, or placebo, were given daily. A sample of each group had serial blood ascorbic acid determinations, which showed significant rises among groups treated with vitamin C, but no difference in mean levels between those receiving 1 and those given 2 g. Although there was no difference between treatment groups in num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2

Year Published

1974
1974
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 5 publications
(2 reference statements)
4
60
2
Order By: Relevance
“…In two studies with children, the vitamin C level in plasma (18) and urine (25) increased in subjects given a placebo (sic!) suggesting that tablets were exchanged by playful children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In two studies with children, the vitamin C level in plasma (18) and urine (25) increased in subjects given a placebo (sic!) suggesting that tablets were exchanged by playful children.…”
Section: Discussionmentioning
confidence: 99%
“…The previous searches were extended by MEDLINE searches to identify newer vitamin C-common cold trials. All placebo-controlled studies using regular vitamin C supplementation with 1 g/day of the vitamin were selected for the present quantitative analysis (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), and the results are shown in Table 1. Regular supplementation refers here to initiating supplementation with healthy people and continuing over the occurring common cold episodes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, important elements of Coulehan's (9) results were explicitly published and can be statistically re-analyzed, in contrast to Dykes and Meier's claims. Furthermore, Coulehan et al (9) found that the duration of colds was 12% and 29% shorter in children administered 1 and 2 g/d of vitamin C respectively suggesting dose dependency up to 2 g/d, but these data were not given by Dykes and Meier (24).…”
Section: Dykes and Meier's 1975 Reviewmentioning
confidence: 98%
“…(24) commented on Coulehan's 1974 study (9) of schoolchildren: "Because the data required for an appropriate analysis are not presented, the statistical significance of the differences reported cannot be considered to have been established." However, Coulehan et al (9) explicitly reported that 32% (61 of 190) of lower grade children administered vitamin C were "never ill on active surveillance," while only 16% (30 of 192) of those administered placebo were never ill. It is highly unlikely that such a difference in favor of vitamin C would be caused purely by chance (P = 0.0002; 2-tailed Fisher's exact test).…”
Section: Dykes and Meier's 1975 Reviewmentioning
confidence: 99%